2012
DOI: 10.1213/ane.0b013e318233041a
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Continuous Noninvasive Measurement of Total, Carboxy, and Methemoglobin Concentration

Abstract: Intraoperative early detection of anemia, identifying toxic levels of carboxyhemoglobin after carbon monoxide exposure and titrating drug dosage to prevent toxic levels of methemoglobin are important goals. The pulse oximeter works by illuminating light into the tissue and sensing the amount of light absorbed. The same methodology is used by laboratory hemoglobinometers to measure hemoglobin concentration. Because both devices work in the same way, efforts were made to modify the pulse oximeter to also measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Normal ranges for smokers have been reported to be Ͻ 2% or Ͻ 3%, but ranges for smokers may be as high as 10 -20%. 20 Unexpectedly, in Weaver's study the mean COHb was 2.67% Ϯ 1.49 percentage points for the 1,053 patients who reported to be non-smokers, and 25% had a COHb Ͼ 3%. The large number of non-smokers with COHb Ͼ 2% suggested that this upper laboratory limit should be reexamined.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Normal ranges for smokers have been reported to be Ͻ 2% or Ͻ 3%, but ranges for smokers may be as high as 10 -20%. 20 Unexpectedly, in Weaver's study the mean COHb was 2.67% Ϯ 1.49 percentage points for the 1,053 patients who reported to be non-smokers, and 25% had a COHb Ͼ 3%. The large number of non-smokers with COHb Ͼ 2% suggested that this upper laboratory limit should be reexamined.…”
mentioning
confidence: 86%
“…Although the authors reported their findings as being within an acceptable range for clinical use, the variable precision is concerning. 20 Pre-hospital screening has previously been demonstrated to be feasible, although clinical outcomes of broad screening have not been described. [21][22] One retrospective review of over 1,700 cases of CO toxicity treated with hyperbaric oxygen demonstrated that patients who were first assessed by pulse CO-oximeter (n ϭ 105 out of 1,711) had a statistically significantly shorter time to blood COHb measurement, by approximately 30 min, and were treated with hyperbaric oxygen an average of one hour earlier than patients who were first assessed by blood COHb.…”
mentioning
confidence: 99%
“…This wavelength is typically used to measure and/or separate the contribution of other hemoglobin forms (met-hemoglobin and carboxy-hemoglobin) as well as other confounder chromophores and dyes in the selected spectral region. 39,40 A common method for studying the oxygenation signal as a function of wavelength is to look at the differences between the optical properties of oxy-and deoxy-hemoglobin. These differences are mainly due to the absorption coefficient, since the scattering properties of blood have been shown to be relatively independent of its oxygen content.…”
Section: Perfusion and Oxygenation Signalmentioning
confidence: 99%
“…However, these devices are leading to correct values only under the condition of the absence of dysfunctional hemoglobin derivatives. A couple of available devices can measure the dysfunctional hemoglobin derivatives COHb and MetHb as well [3,4]. These devices use a higher number of LEDs.…”
Section: Introductionmentioning
confidence: 99%